2020
DOI: 10.1088/1361-648x/ab86f1
|View full text |Cite
|
Sign up to set email alerts
|

Topological and thermoelectric properties of double antiperovskite pnictides

Abstract: Doubling the perovskite cell (double perovskite) has been found to open new possibilities for engineering functional materials, magnetic materials in particular. This route should be applicable to the antiperovskite (aPV) class. In the pnictide based double aPV (2aPV) class introduced here magnetism is very rare, and we address them as new topological materials, possibly with thermoelectric interest. We have found that the 2aPV supercell provides a systematically larger band gap that can serve to inhibit bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the realm of thermoelectronics, thermoelectric generators (TEGs) have the potential to extract usable energy from numerous sources, such as industrial operations, power production, and transportation systems. Considerable study has been undertaken on many types of thermoelectric materials, including tin selenide [13], chalcogenides [14][15][16], half-Heusler alloys [17,18], Zintl phases [19], perovskites [20][21][22], and additional materials [23][24][25]. However, high operating temperatures, cost per watt, and structural complexity have hindered the widespread industrial application of these materials, despite significant progress in improving their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of thermoelectronics, thermoelectric generators (TEGs) have the potential to extract usable energy from numerous sources, such as industrial operations, power production, and transportation systems. Considerable study has been undertaken on many types of thermoelectric materials, including tin selenide [13], chalcogenides [14][15][16], half-Heusler alloys [17,18], Zintl phases [19], perovskites [20][21][22], and additional materials [23][24][25]. However, high operating temperatures, cost per watt, and structural complexity have hindered the widespread industrial application of these materials, despite significant progress in improving their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…When the A cation is divalent, the Y and X anions can be divalent and tetravalent, respectively, as exemplified by Ca 3 OPb, , or trivalent and trivalent, respectively, as exemplified by Ca 3 NSb. , When the A cation is monovalent, the Y and X anions are divalent and monovalent, respectively, as exemplified by Na 3 OCl , and Ag 3 SI. , So far, many antiperovskites have been synthesized, exhibiting a variety of physical properties such as ionic conductivity, magnetism, superconductivity, and negative thermal expansion. , However, for prospective optoelectronic applications, the best-known A 3 OX oxyhalide antiperovskites generally exhibit large bandgaps due to their too strong ionicity . It is expected that replacing each of two octahedral O anions with a combination of two other anions (denoted as Y′ and Y″) to form double antiperovskites A 6 Y′Y″X 2 , where the Y′ and Y″ anions at the octahedral centers are arranged orderly, may enable an effective bandgap engineering for potential optoelectronic applications and further expand the family of antiperovskites. , …”
Section: Introductionmentioning
confidence: 99%
“…Sattar et al [14] have investigated structural, electronic, mechanical and thermoelectric parameters of A 3 OX (where A = Li, Na and K; X = Cl, Br and I) antiperovskite compound and stated that all compounds are mechanically and thermodynamically stable and offer a fertile base that can enhance overall thermoelectric output for thermoelectric devices and renewable energy production. Goh et al [15] have studied topological and TE parameters of double antiperovskite compounds and found these materials a good candidate for TE applications. We have observed that in contrast to mostly using conventional sources, the efficiency of the TE devices is quite low.…”
Section: Introductionmentioning
confidence: 99%
“…From the above literature review, we can conclude that TE devices may turn out to be an appropriate device for green and renewable energy sources, hence we are looking forward to a suitable double antiperovskite composite that may be used in TE devices. These types of compounds have also been explored for topological properties and storage devices [15, 18] but there is a lack of investigation of their TE properties. Hence, we have investigated thermoelectric properties of cubic double antiperovskite structure X 6 SOA 2 (X = Na, K; A = Cl, Br and I) for the very first time by using density functional theory implemented in WIEN2k code.…”
Section: Introductionmentioning
confidence: 99%